PENGARUH DIMENSI KARAKTERISTIK KOMUNITAS VIRTUAL TERHADAP COMMUNITY COMMITMENT DAN LOYALITAS PENGGUNA KAMERA DSLR MEREK CANON - ILHAM ADIPRADANA; MUCHSIN SAGGAF SHIHAB (Program Studi Magister Manajemen FE Unsri, 2013)
This study aims to analyze the effect of dimensions of virtual community characteristics (i.e. interactivity, system quality, information reliabity, and reward for activity) on community commitment and consumers’ loyalty. The concepts of virtual community characteristics, community commitment and loyalty were taken from various resources. This research is quantitative and explanative in nature. Target respondents were the the users of Canon DSLR camera. Using a convenience sampling technique, a total of 100 responses were obtained. Based on multiple regression analysis, it was found that except system quality other dimensions of virtual community characteristics partially had positive effect on community commitment. In addition, it was also found that the dimensions of virtual community collectively had significant effect on community commitment and that community commitment had positive and significant effect on loyalty.